Chapter: 'Ten Theses on the Subject of Biology and Politics: Conceptual, Methodological, and Biopolitical Considerations' from book: The Palgrave Handbook of Biology and Society - Samantha Frost (Palgrave Macmillan, 2017)
In this chapter, I develop a set of concepts and methodological principles that researchers might draw on as they try to elucidate the processes by which the engagement of humans with their social worlds, material environments, and historical cultures results in the formation of a self in subject, corporeal, and biological dimensions. I forge a conceptual language and rules for analysis that may enable scholars to negotiate converging accounts of how the social norms, lived environments, and power relations through which people develop a sense of self are bound up with processes through which biological organisms compose and recompose themselves over time.